Characteristics of Tomato Sauce with Various Concentrations of Breadfruit Starch (Artocarpus communis) as a Natural Thickener - Indri Triastuti; Hartati, Sri; Asmoro, Novian Wely (Fakultas Pertanian Universitas Veteran Bangun Nusantara, 2024)
Tomato sauce is a food product made in the form of tomato paste. Making tomato sauce requires a thickener. The thickener commonly used in making tomato sauce is CMC (Carboxymethyl Cellulose) which does not contain elements that are beneficial to health. One natural thickening agent that has the potential to be developed is breadfruit starch. This research aims to determine the effect of adding breadfruit starch on the characteristics of tomato sauce. The research began with making breadfruit starch, then making tomato sauce according to the treatment and continued with product analysis. This study used a simple complete random design with one factor, namely S(0.5) as much as 2.5 grams of breadfruit starch, S(1.0) as much as 5 grams of breadfruit starch, S(1.5) as much as 7.5 grams of breadfruit starch, SM (0 grams added breadfruit starch/using 5 grams of cornstarch), and SK (commercial tomato sauce). The data obtained were analyzed using One Way Anova and to determine whether there were differences in treatment, the Duncan Multiple Range Test (DMRT) was continued with a significance level of 5%. The results showed that the addition of breadfruit starch had a significant effect on water content S(1.5) with a value of 76.87%, degree of acidity/pH S(0.5) with a value of 4.01, total dissolved solids S(1.5 ) with a value of 27°Brix.